Carbon Emission of Energy Efficient Residential Building. (2015) - Hu, Fan; Zheng, Xuejing
Abstract: Carbon emission of residential buildings is calculated based on LCA (life cycle assessment). The influence factors, such as the insulation thickness, air conditioning form and service life are analyzed. A typical energy efficient residential building was selected to calculate its carbon emission in different conditions. In this case, when the insulation thickness is 100 mm, the life cycle carbon emission is the minimum. In other words, each residential building has its optimum insulation thickness. And with the building service life extending, the emission will decrease. As for the air conditioning forms, the results show that the carbon emission of residential building with split air conditioning is less than with centralized air conditioning.